Implementation of E-SKCK by Sat Intelkam to Improve Services to the Community in the Cirebon Polresta Jurisdiction - Hadi, Muhamad (Police Studies Review, 2024)
The development of internet based technology based on government applications is commonly called E- Government. The Indonesian police force use internet technology to carry out its commission in the form of an online police record release service known as E- SKCK. One of Polres that gave E- SKCK service was Polresta Cirebon. The E- SKCK service at Polresta Cirebon has not been maximum, so the writer does research on application and factors causes the problem and provides some suggestion for improvement so E- SKCK service kan be improved. Research is done by field research, by observing firsthand the places, facilities, manufacturing, and the obstacles. The method is a qualitative method in which foregleam of the implementation of the E- SKCK sevice. Data obtained using document study tecniques, interviews, and observations. Studies show that the application of E- SKCK at Polresta Cirebon may not have been high as reflected in the data obtained during the research. Writing the thesis used puvlic service theory and management theory and employed two concepts of public service and E- SKCK concepts. Studies have been found that there are still a lot of E- SKCK services in the Polresta Cirebon, betweenwhich there are still limited facilities at thecenter server in the mabes, which hasnot been corrected by the vendor and where there is a lack of E-SKCK sevices to society that people still think E- SKCK is more complex than manual SKCK. The recent invrease in the number of SKCK applicants can also be seen from the greater number of SKCK applicants to the E-SKCK, ehich is the manual SKCK 93320 petitioners and E- SKCK through 21 petitioners. On the basic of the lack of E-SKCK service, the writer gives some advice that can provide the solution to the problem. Soome of them increased the quality of facilities and places of E- SKCK serveces, coordinating with vendors and improving network quality on servers, distributing brochures and pamphlets about E- SKCK services and conducting publications over the internet.